New syntaxon names for the Italian Quercus cerris woods - Terzi, Massimo; Ciaschetti, Giampiero; Fortini, Paola; Rosati, Leonardo; Viciani, Daniele; Di Pietro, Romeo (Mediterranean Botany, 2021)
Based on the results of a previous nomenclatural revision of the Italian Quercus cerris forests, 31 syntaxon names are here validated or described as new and 5 lectotypes are designated.